VEGETATIVE NERVOUS SYSTEM. SYMPATHETIC AND PARASYMPATHETIC DIVISIONS - Ropijonova Farzona; Abdurakhmanova Aziza; Pulatov Khabibulla (Western European Studies, 2025)
The vegetative nervous system (VNS) provides regulation of internal organs and maintains the body’s homeostasis. It consists of the sympathetic and parasympathetic divisions, each performing specific functions. The sympathetic division activates the “fight or flight” response, increases heart rate, raises blood pressure, and mobilizes energy resources. The parasympathetic division ensures restoration and rest, decreases heart rate, and promotes digestion. This article examines the morphological structure of the VNS, neurotransmitters, regulation mechanisms, clinical significance, and recent research on the influence of the sympathetic and parasympathetic divisions on the functional systems of the body
Keywords: vegetative nervous system; sympathetic system; parasympathetic system